Reliability aspects in operational structuring of large-scale urban distribution systems - Strbac, G; Nahman, J (Second International Conference on the Reliability of Transmission and Distribution Equipment, 1995)
Distribution systems largely determine the service quality profile seen by end-customers and dominate overall reliability indices. The most frequent and most significant outages are those in the medium voltage feeder sections. This paper underlines the importance of the incorporation of service quality requirements into operational planning and structuring of medium voltage urban power networks. The network configuration problem is defined as a constrained multiobjective optimization problem where service interruption costs, load imbalance among feeders and transformers as well as real power losses are minimized subject to security and operational constraints. A fuzzy coordination technique is used to obtain a suitable balance between the conflicting and incomparable objectives. The proposed concept is tested on a slightly modified actual underground distribution system.